(3GJNGP GdbQGQGJ GdGOGQjI (B/s - (3MLGMLI, Ydj Ndbs ((3YeGf(B: s (3OGQ bfOjd(B, s, 2010)
(3eaghe GdbQGQG GdGOGQj h CfhGYg , GdbQGQ h GdeYdheGJ , GdbQGQ GdLeGYj h GdbQGQ GdaQOj , GdeTGQcI aj GJNGP GdbQGQGJ , eTGcd h eYhbGJ GJNGP GdbQGQGJ aj GdOhd GdfGejI , JfajP GdbQGQGJ GdGOGQjI h fgGjJgG bQGQ NUNUI GdGJUGdGJ GdCQOfjI h GdBKGQ GdfGLeI Yf gPG GdbQGQ (B( (3MGdI YedjI (B).(3GdbQGQGJ GdGOGQjIs
Keywords: (3GJNGP GdbQGQs; (3EOGQI GdCYeGds; (3GdbQGQGJ GdEOGQjIs